ANALYSIS OF RELATIONSHIP BETWEEN PRODUCTION FACTORS AND PRODUCTION TILAPIA FARMING BUSINESS IN TOBA SAMOSIR REGENCY - Sukma Aditya Sitepu (AGRITROPICA : Journal of Agricultural Sciences, 2019)
ABSTRACTThis study aims to analyze the relationship between floating net cage size, labor, feed, seeds and medicine with tilapia production in Toba Samosir Regency. The selection of the study area was carried out purposively because Toba Samosir district was a tilapia aquaculture area that had the largest harvest area in North Sumatra. The data used are secondary data and primary data obtained in the study area. The analytical method used is Chi-Square analysis using SPSS 18.0 software. The results of this research are floating net cage areas, labor, feed, seeds, and medicines used in relation to the production of tilapia fish in floating net cages in Toba Samosir District significantly. With the closeness of the relationship between the extent of Floating Net Cages, feed, medicine with a production of 78.7%, and the closeness of the relationship of seeds with production 89.2 and the closeness of labor relations with a production 70.4%.Keywords: Floating Net Cages, Production, Production Factors, Tilapia.